Initial Experience with Sildenafil, Bosentan, and Nitric Oxide for Pediatric Cardiomyopathy Patients with Elevated Pulmonary Vascular Resistance before and after Orthotopic Heart Transplantation - Babak Daftari; Juan Carlos Alejos; Gregory Perens (Journal of Transplantation)
Background. Although pulmonary hypertension complicating dilated cardiomyopathy has been shown to be a significant risk factor for graft failure after heart transplantation, the upper limits of pulmonary vascular resistance (PVR) that would contraindicate pediatric heart transplantation are not known. Methods. A retrospective review of all pediatric orthotopic heart transplant (OHT) performed at our institution from 2002 to 2007 was performed. Seven patients with PVR >6 Wood's units (WU) prior to transplant were compared pre- and postoperatively with 20 matched controls with PVR <6 WU. All pulmonary vasodilator therapies used are described as well as outcomes during the first year posttransplant. Results. The mean PVR prior to transplantation in the 7 study cases was 11.0±4.6 (range 6–22) WU, compared to mean PVR of 3.07±0.9 WU (0.56–4.5) in the controls (𝑃=.27×10−6). All patients with elevated PVR were treated pre-OHT with either Sildenafil or Bosentan. Post-OHT, case patients received a combination of sildenafil, iloprost, and inhaled nitric oxide. All 7 case patients survived one year post-OHT, and there was no statistical difference between cases and controls for hospital stay, rejection/readmissions, or graft right ventricular failure. Mean PVR in the cases at one and three months post-OHT was not significantly different between the two groups. Only one of the cases required prolonged treatment with iloprost after OHT. Conclusions. A PVR above 6 WU should not be an absolute contraindication to heart transplantation in children.